Development Direction of New Energy Vehicle Charging Technology based on Electronic Power Technology - Jia, Churuo (International Journal of Mechanical and Electrical Engineering, 2024)
The improvement of charging technology is necessary. By listing the charging characteristics of the three charging modes, this paper gives the methods to improve the charging efficiency of new energy vehicles in each mode, the advantages and disadvantages of the mode to improve the charging efficiency, and what kind of technology is expected to be used in the future. By summarizing the development prospects of various charging methods, providing the direction of building a more energy-efficient charging system in the future, and looking forward to the possible vigorous development of charging modes in the future.